Research on Pandemics 2021
DOI: 10.4324/9781003214687-7
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Firm Performance

Abstract: Using the financial data of listed Chinese companies, we study the impact of COVID-19 on corporate performance. We show that COVID-19 has a negative impact on firm performance. The negative impact of COVID-19 on firm performance is more pronounced when a firm's investment scale or sales revenue is smaller. We show, in an additional analysis, that the negative impact of COVID-19 on firm performance is more pronounced in serious-impact areas and industries. These findings are among the first empirical evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…This triggers an increasingly difficult crisis because it results in a decrease in individual income which also reduces people's purchasing power for goods and services. In line with the research of (Devi et al, 2020;Shen et al, 2020) (Devi et al, 2020); (Atayah & Frederico, 2021) it was found that the company's performance was declining due to the COVID-19 pandemic. ROA and revenue as a form of representation of company performance in this study show declining results from 2019 to 2020 due to the decline in people's income and the weakening of people's purchasing power which affects the income of companies in Indonesia which is also decreasing.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…This triggers an increasingly difficult crisis because it results in a decrease in individual income which also reduces people's purchasing power for goods and services. In line with the research of (Devi et al, 2020;Shen et al, 2020) (Devi et al, 2020); (Atayah & Frederico, 2021) it was found that the company's performance was declining due to the COVID-19 pandemic. ROA and revenue as a form of representation of company performance in this study show declining results from 2019 to 2020 due to the decline in people's income and the weakening of people's purchasing power which affects the income of companies in Indonesia which is also decreasing.…”
Section: Discussionsupporting
confidence: 65%
“…The decline in the company's financial performance was reflected in a decrease in investment value and decrease in income. (Shen et al, 2020) also found that the sectors most affected by COVID-19 in China were the tourism, catering, and transportation sectors. (Hu & Zhang, 2021) researched the effect of the COVID-19 outbreak on company performance in 107 countries.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Kinerja perusahaan sangat bergantung pada kemampuan manajemen untuk menghasilkan dan mengelola sumber daya yang unik dan spesifik untuk bersaing dan bertahan dalam berbagai situasi (Devi et al, 2020). Menurut (Shen et al, 2021), untuk membantu kinerja keuangan perusahaan pertambangan di China dari berbagai situasi ekonomi yang berisiko, perlu diciptakan keunggulan kompetitif baru untuk pembangunan jangka panjang. Penelitian mengenai kondisi keuangan bank ketika sebelum dan selama terjadinya pandemi covid-19 maupun penelitian terkait pengaruh pandemi covid-19 pada kinerja bank telah dilakukan.…”
Section: Pendahuluanunclassified